The effect of halal labels on Muslim consumers' purchase decision for cough medicines - Shabrina, Nadhilah Nur; Ali, Khalifah Muhammad; Mahanani, Yekti (IPB University, 2024)
Indonesia, a country with a predominantly Muslim population, mandates halal certification for all products that are entering, circulating, and trading within its territory, including medicines with several critical halal points. Therefore, this research aimed to better understand the characteristics of Muslim consumers in DKI Jakarta as well as the factors that affected purchase decision for cough medicines. A total of 100 respondents were surveyed, and the collected data were analyzed using descriptive analysis and structural equation modeling partial least squares (SEM-PLS). The results showed that halal labels, personal factors, and products quality all had a substantial effect on DKI Jakarta Muslim consumers' purchase decision for cough medicines. However, social and psychological factors had limited impact on the decision.